Mediterranean voyages : the archaeology of island colonisation and abandonment - Dawson, Helen (Helen Sarah) (Walnut Creek, CA : Left Coast Press, Inc., 2014)
"Islands are ideal case studies for exploring social connectivity, episodes of colonisation, abandonment, and alternating phases of cultural interaction and isolation. Their societies display different attitudes toward the land and the sea, which in turn cast light on group identities. This volume advances theoretical discussions of island archaeology by offering a comparative study of the archaeology of colonisation, abandonment, and resettlement of the Mediterranean islands in prehistory. This comparative and thematic study encourages anthropological reflections on the archaeology of the islands, ultimately focusing on people rather than geographical units, and specifically on the relations between islanders, mainlanders, and the creation of islander identities. This volume has significance for scholars interested in Mediterranean archaeology, as well as those interested more broadly in colonisation and abandonment"--
Machine generated contents note: Acknowledgments Chapter 1: Island archaeologiesChapter 2: The Mediterranean: physical and cultural spacesChapter 3: Theories of colonisationChapter 4: The colonisation of the Mediterranean islandsChapter 5: Redefining island colonisationChapter 6: Theories of abandonmentChapter 7: Islands in timeChapter 8: Mediterranean voyagesReferencesIndex.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Island archaeology -- Mediterranean Region; Prehistoric peoples -- Mediterranean Region; Antiquities, Prehistoric -- Mediterranean Region; Excavations (Archaeology) -- Mediterranean Region; Mediterranean Region -- Colonization; Electronic books